(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
Background and Aim. Individual genetic polymorphisms demonstrate only moderate predictive accuracy for liver cirrhosis (LC) in chronic hepatitis C (CHC). Polygenic approaches that combine multiple loci covering distinct pathogenetic pathways may substantially improve risk prediction. This study aimed to develop a combined genetic risk score based on five polymorphisms (TNF-α G308A, IL28B C/T, VEGFA C936T, MMP9 Gln279Arg, SOD2 Ala16Val) and to evaluate its diagnostic performance in comparison with individual loci and standard clinical indices. Materials and Methods. 93 CHC patients were enrolled: Group I comprised 48 patients without cirrhosis (F0–F3 by METAVIR) and Group II comprised 45 patients with verified cirrhosis (F4). All five loci were genotyped by real-time PCR with TaqMan probes. A cumulative score (0–10) was calculated by assigning 0–2 points per locus (0 = protective homozygote, 1 = heterozygote, 2 = risk homozygote). ROC analysis with AUC calculation was performed. AUC comparisons were made using the DeLong method. Results. A score ≥6 was found in 64.4% of cirrhosis patients vs. 16.7% of non-cirrhotic patients (χ²=22.87; p<0.001; OR=9.29; 95% CI 3.37–25.6; RR=3.86; 95% CI 1.89–7.90). The combined score AUC was 0.79 (95% CI 0.70–0.87), significantly exceeding each individual polymorphism (p=0.003–0.04). Integration with APRI >1.0 yielded AUC=0.86 (95% CI 0.78–0.93), specificity 91.7%, and PPV 87.5%. The genetic score correlated with MELD (r=0.47; p<0.001), APRI (r=0.52; p<0.001), and liver stiffness by elastography (r=0.56; p<0.001). Conclusion. The combined genetic risk score substantially outperforms individual polymorphism analysis and provides clinically meaningful prediction for LC formation.